FoxP3 and IDO in Canine Melanocytic Tumors. Issue 2 (March 2019) - Porcellato, Ilaria; Brachelente, Chiara; De Paolis, Livia; Menchetti, Laura; Silvestri, Serenella; Sforna, Monica; Vichi, Gaia; Iussich, Selina; Mechelli, Luca
Human melanoma is one of the deadliest forms of cancer, with poor prognosis and high resistance to chemotherapy and radiotherapy. The discovery of immunosuppressive mechanisms in the human melanoma microenvironment led to the use of new prognostic markers and to the development of immunotherapies targeting immune checkpoint molecules. Immunoescape mechanisms in canine melanoma have not yet been investigated, and no such immunotherapy has been tested. The aim of this study was to provide preliminary data on the expression of transcription factor forkhead box protein P3 (FoxP3) and indoleamine 2, 3-dioxygenase (IDO) in primary canine melanocytic tumors and to investigate their prognostic role. Formalin-fixed, paraffin-embedded samples from 74 canine melanocytic tumors (26 oral melanomas, 23 cutaneous melanomas, and 25 cutaneous melanocytomas) were retrospectively evaluated by immunohistochemistry to explore the expression of FoxP3 and IDO. An increased risk of death due to melanoma was associated with a higher number of FoxP3 + cells per high-power field (FoxP3 + /HPF), a higher percentage of CD3 + cells that were also FoxP3 + infiltrating and surrounding the tumor (%FoxP3), and a higher number of IDO + cells/HPF (IDO + /HPF). A prognostic value for FoxP3 and IDO is suggested by our study, with optimal cutoffs of 14.7 FoxP3 + cells/HPF, 6.1 IDO + cells/HPF, and 12.5% FoxP3 + cells. Both markers were also associated with tumor type. Multivariable analysis identified IDO + /HPF ( P < .001) as an independent prognostic marker. Even though stratification by diagnosis caused a loss of significance, results from the present study suggest a prognostic role for IDO and FoxP3, possibly related to the establishment of an immunosuppressive microenvironment.